Hubungan Asupan Lemak, Lingkar Perut dan Aktifitas Fisik dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Rawat Inap Simpang Tiga Kota Pekanbaru dan Tinjauannya Menurut Pandangan Islam - Dahriza, Munziri Ilman; Indriarti, Werda; Machmud, Amir (Junior Medical Journal, 2024)
Based on data from the health profile of Pekanbaru City in 2019, the prevalence of hypertension sufferes with an average of 28.20%. where the highest number is in the Simpang Tiga Inpatient Health Center at 29.6%. Hypertension is a disease characterized by increased arterial blood pressure more than normal. Factors that can cause hypertension, these risk factors include age, gender, family history, obesity, hilg salt levels, fat intake, physical activity, smoking and dringking alcohol. This research is a quantitative approach with correlation analytic. The population in this study were all people who visited the Work area of the Simpang Tiga Inpatient Health Center Pekanbaru City from July to December 2020 as many as 327 people. The sampling technique used is accidental random sampling. Through the results of bivariate testing in this study, it was found that fat intake with a P-value of 0.026, abdominal circumference with a P-value of 0.031 and fat intake with the incidence of hypertension in the work area of the Simpang Tiga Inpatient Health Center Pekanbaru City with a P value of – Value of 0.000. from the research conducted there is a significant relationship between fat intake, abdominal circumference, and physical activity with the incidence of hypertension in the work area of the Simpang Tiga Inpatient Health Center Pekanbaru City.